Cardiac Monitoring and Heart Failure in Advanced Breast Cancer Patients Treated With Trastuzumab in Ontario, Canada - Rushton, Moira; Kappel, Coralea; Lima, Isac; Tuna, Meltem; Pritchard, Kathleen; Hawken, Steven; Dent, Susan (Frontiers in Cardiovascular Medicine, 2022)
Background Trastuzumab has improved patient outcomes in HER2 + breast cancer (BC) but carries a risk of cardiotoxicity. Routine cardiac imaging is recommended for advanced breast cancer (aBC) patients during trastuzumab treatment despite a lack of evidence that this improves patient outcomes. This study was conducted to understand predictive factors for cardiac events and determine the impact of cardiovascular monitoring in aBC. Methods This retrospective population-based cohort study included aBC patients treated with trastuzumab (all lines), in Ontario, Canada from 2007 to 2017. The overall cohort was divided into two groups; those who developed a cardiac event (CE) vs. those who did not. Patients with pre-existing heart disease were excluded. Logistic regression was performed to identify patient characteristics associated with an increased risk of CE. Results Of 2,284 patients with HER2 + aBC treated with trastuzumab, 167 (7.3%) developed a CE. Median age at first dose of trastuzumab was 57 (IQR 49–66); 61 (IQR 51–70) for patients with a CE. Median number of cycles was 16 (IQR 7–32); 21 (IQR 8–45) for patients with a CE (p < 0.01). Twelve (0.5%) patients died of cardiac causes; all had a prior CE. Increased risk of CEs was associated with age > 60 (OR 5.21, 95% CI 1.83–14.84, p = 0.05) and higher number cycles of trastuzumab (OR 1.01; 95% CI 1–101, p = 0.028). Conclusion This is the first population-based study to report on CEs and cardiac monitoring in HER2 + aBC patients during trastuzumab-based therapy. Older age and longer treatment with trastuzumab were associated with an increased risk of a CE.